2019
DOI: 10.1111/psyp.13421
|View full text |Cite
|
Sign up to set email alerts
|

Interoception, conditioning, and fear: The panic threesome

Abstract: The present article aims to illustrate and review evidence on how associative learning involving interoceptive stimuli (interoceptive conditioning) can lead to changes in physiological, emotional, and perceptual outcomes. We first outline a functional perspective on Pavlovian conditioning and provide a general introduction and historical background on interoceptive conditioning as a special instance of Pavlovian conditioning. Next, biological and learning accounts of panic disorder are discussed, followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 173 publications
1
17
0
Order By: Relevance
“…Clinical observations and collective evidence from challenge studies in the laboratory, neuroimaging, symptomology, treatment responses and translational animal models have led to an increased understanding of PD (11,12,14,(18)(19)(20)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). As illustrated in Figure 1, PD frequently originates with patients experiencing spontaneous panic attacks that seem to occur without an explicit trigger.…”
Section: Relevance Of Interoception and Conditioned Fear In Panic Dis...mentioning
confidence: 99%
“…Clinical observations and collective evidence from challenge studies in the laboratory, neuroimaging, symptomology, treatment responses and translational animal models have led to an increased understanding of PD (11,12,14,(18)(19)(20)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). As illustrated in Figure 1, PD frequently originates with patients experiencing spontaneous panic attacks that seem to occur without an explicit trigger.…”
Section: Relevance Of Interoception and Conditioned Fear In Panic Dis...mentioning
confidence: 99%
“…Based on the studies outlined above, as well as similar research in tonic pain (Hansen et al., 2017), alpha/lower beta desynchronization (possibly scaling to dyspnea unpleasantness), together with higher beta and gamma synchronization (possibly reflecting an increase in respiratory effort) might be expected (see Table 1). Such spontaneous dynamics could also be investigated when dyspnea is only anticipated (for instance by utilizing conditioning designs, see Van Diest, 2019). Depending on the design, we could expect alpha and beta activity to reflect the predicted occurrence and/or intensity of dyspnea.…”
Section: How Neural Oscillations May Help To Explain Dyspnea: Future ...mentioning
confidence: 99%
“…A large number of psychiatric disorders [e.g., anxiety (Paulus and Stein, 2010 ), panic disorder (Van Diest, 2019 ), obsessive-compulsive disorder (Yoris et al, 2017 ), and depersonalization (Sedeño et al, 2014 )], somatic symptom disorders (Witthöft et al, 2020 ), neuro-developmental disorders [e.g., attention-deficit hyperactivity disorder (Kutscheidt et al, 2019 )], autism spectrum disorders (DuBois et al, 2016 ), and eating disorders [e.g., anorexia nervosa (Jacquemot and Park, 2020 ) and bulimia nervosa (Klabunde et al, 2017 )], as well as depression (Paulus and Stein, 2010 ), posttraumatic stress disorder (Nicholson et al, 2016 ), and substance use disorders (Paulus et al, 2013 ), have all been linked to interoceptive dysfunction. Although few in number, several studies have confirmed the association between interoceptive dysfunction and neurodegenerative diseases, including Alzheimer's disease (AD) (García-Cordero et al, 2016 ; Salamone et al, 2021 ), behavioral variant frontotemporal dementia (García-Cordero et al, 2016 ; Salvato et al, 2018 ; Salamone et al, 2021 ), and Parkinson's disease (Salamone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%